Psychological characteristics of health-related quality of life among retired elite athletes in Nigeria (2021)
Retirement from sport is inevitable and unavoidable. It is a major source of threat to the health-related quality of life of retired elite athletes especially among who refute involvement in adequate planning and preparation for life after sports. The purpose of this study was to examine psychological characteristics of health-related quality of life (HRQoL) among retired elite athletes in Oyo State, Nigeria. Two hypotheses were tested. The study employed descriptive survey research design. Purposive sampling technique was used to select one hundred (100) (Male = 63, Female = 37) retired elite athletes. The standardized questionnaires of Athletic Identity Measurement Scale (AIMS), Centre for Epidemiologic Studies-Depression Scale (CES-DS) and the Short-Form 8 (SF-8) Health Survey were used for collection of data from the respondents. The reliability coefficient of the instrument used are 0.86, 0.84 and 0.88 respectively. Data were analysed using descriptive and inferential statistics of frequency counts, percentages and multiple regression. The result of the study showed that, there is significant joint contributions of psychological characteristics on HRQoL (F(2, 97) = 107.581, R = .74, R2 = .686, Adj R2 = .686, p<0.05) with 68.6% of degree of variance. Also, there is significant relative contributions of psychological characteristics [athletic-identity (p = -0.079, t = 0.41, p < .05) and depression (p = -.297, t = -1.521, p<0.05)] on HRQoL. Based on the findings, it was concluded that psychological intervention programme that promotes HRQoL and prepares retired elite athletes for life after sports should be developed and inculcated into the elite athletes' programme before retirement, while regular visitation to psychological and mental health care centres for optimum advise on health-related wellbeing should carried out by the retired elite athletes